Highly absorbing multispectral near-infrared polymer nanoparticles from one conjugated backbone for photoacoustic imaging and photothermal therapy. (November 2017) - Chen, Haobin; Zhang, Jian; Chang, Kaiwen; Men, Xiaoju; Fang, Xiaofeng; Zhou, Libo; Li, Dongliang; Gao, Duyang; Yin, Shengyan; Zhang, Xuanjun; Yuan, Zhen; Wu, Changfeng
Abstract: Semiconducting polymers with specific absorption are useful in various applications, including organic optoelectronics, optical imaging, and nanomedicine. However, the optical absorption of a semiconducting polymer with a determined structure is hardly tunable when compared with that of inorganic semiconductors. In this work, we show that the optical absorption of polymer nanoparticles from one conjugated backbone can be effectively tuned through judicious design of the particle morphology and the persistence length of polymers. Highly absorbing near-infrared (NIR) polymers based on diketopyrrolopyrrole-dithiophene (DPP-DT) are synthesized to have different molecular weights (MWs). The DPP-DT polymer with a large molecular weight and high persistence length exhibited remarkably high optical absorption with a peak mass extinction coefficient of 81.7 L g −1  cm −1, which is one of the highest value among various photothermal agents reported to date. Particularly, the polymer nanoparticles with different sizes exhibit broadly tunable NIR absorption peaks from 630 to 811 nm. The PEGylated small polymer dots (Pdots) show good NIR light-harvesting efficiency and high non-radiative decay rates, resulting in a relatively high photothermal conversion efficiency in excess of 50%. Thus, this Pdot-based platform can serve as promising photothermal agents and photoacoustic probes for cancer theranostics. Graphical abstract: